1975
DOI: 10.2170/jjphysiol.25.525
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Influence on Palmar Sweating and Mental Influence on Generalized Sweating in Man

Abstract: Sweat rates on the forearm and on the palm were simultaneously recorded by resistance hygrometry and the mode of sweating in these areas in response to thermal and non-thermal stimuli were compared with each other. In Series A, periodic infrared irradiation (1min on, 1min off) was done to the back of the trunk, and reflex responses in sweat rate were recorded on both test areas. A high correlation was noted between the mean changes in the palmar sweat rate and those in the forearm one during the irradiation cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 11 publications
2
59
2
Order By: Relevance
“…It is known that mental stress can induce sweating responses even in nonglabrous skin (28,33), and it was demonstrated recently that both thermal and psychologenic sweating may share a common descending pathway in the brain stem (11). Therefore, the potential influence of mental stress on nonglabrous sweating during passive stretches could not be eliminated in the present study, although the passive calf muscle stretches did not increase the ⌬SR palm , which may be sensitive to mental stress.…”
Section: Discussioncontrasting
confidence: 52%
“…It is known that mental stress can induce sweating responses even in nonglabrous skin (28,33), and it was demonstrated recently that both thermal and psychologenic sweating may share a common descending pathway in the brain stem (11). Therefore, the potential influence of mental stress on nonglabrous sweating during passive stretches could not be eliminated in the present study, although the passive calf muscle stretches did not increase the ⌬SR palm , which may be sensitive to mental stress.…”
Section: Discussioncontrasting
confidence: 52%
“…Mean skin temperature ( -Tsk) was calculated according to the method of Hardy & Dubois (1938). The SR on the three body sites was measured continuously by the ventilated capsule method (Van Beaumont & Bullard, 1963;Nadel et al 1971;Ogawa, 1975;Yamazaki et al 1994;Kondo et al 1998). Dry nitrogen gas was supplied to three capsules (chest and forearm: 7·06 cmÂ; palm: 1·53 cmÂ) at a rate of 1·5 l min¢ and the humidity of the nitrogen gas flowing out of the capsules was measured using a capacitance hygrometer (HMP 133Y; Vaisala, Finland).…”
Section: Measurementsmentioning
confidence: 99%
“…However, there is no actual evidence that the sweating response is modulated during activation of the muscle metaboreflex in hyperthermia (when sweating has already been initiated). Furthermore, although the sweating response in the hairy regions is known to differ from that in hairless regions (palm and foot), where mental and emotional sweating occurs (Kuno, 1956;Ogawa, 1975;Sakakibara et al 1989), regional differences in the effect of the muscle metaboreflex on the thermoregulatory sweating response have not previously been studied. The purpose of this study was to examine whether the thermoregulatory sweating response can be modulated by the muscle metaboreflex and if so, whether there are any regional differences in the modulation of the response.…”
mentioning
confidence: 99%
“…However, the initiation of dynamic exercise (7,19,31) and brief isometric exercise (3,17,28) under warm environmental conditions can increase the sweating rate (SR) without marked changes in the thermal factors. This indicates that sweating responses are due mainly to alterations in nonthermal factors that are associated with mental stress (23,36), central command (7,19,31,34,36), and stimulation of mechanosensitive (7,19,31) or metabosensitive (3,18,28) factors in exercising muscle. Also, it is suggested that the nonthermal sweating response during exercise is a feedforward mechanism of thermoregulation, because this response precedes changes in the thermal factors (31,36).…”
mentioning
confidence: 99%